2023
DOI: 10.1098/rsta.2023.0134
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of international border control measures during the COVID-19 pandemic: a narrative synthesis of published systematic reviews

Karen Ann Grépin,
John Aston,
Jacob Burns

Abstract: The effectiveness of international border control measures during the COVID-19 pandemic is not well understood. Using a narrative synthesis approach to published systematic reviews, we synthesized the evidence from both modelling and observational studies on the effects of border control measures on domestic transmission of the virus. We find that symptomatic screening measures were not particularly effective, but that diagnostic-based screening methods were more effective at identifying infected travellers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…These two variants were normally distributed when the normal plot of the residuals was examined, and the data were without outliers (Figure 1). [10,16]. Stressing this point, it has been reported that COVID-19 cases were found among travelers crossing Turkey to Iraq [11], without attempting to delineate the SARS-CoV-2 variants infecting them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two variants were normally distributed when the normal plot of the residuals was examined, and the data were without outliers (Figure 1). [10,16]. Stressing this point, it has been reported that COVID-19 cases were found among travelers crossing Turkey to Iraq [11], without attempting to delineate the SARS-CoV-2 variants infecting them.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported 22 distinct mutations of SARS-CoV-2 spike protein regions between 2020 to 2021 in Iraq isolates, with the majority of the variants belonging to B.1.1.7 lineage [9]. Border gates are focal points of disease entry among neighboring states [10]. A recent study from the Kurdistan Region, Iraq reported the occurrence of COVID-19 cases among travelers crossing the Iraqi border from Turkey (August 21, 2020, to August 21, 2021), without any attempt to detect the SARS-CoV-2 variants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most evidence was due to modelling studies with a lack of ‘real world’ data (Burns et al, 2021), with inconsistent parameter estimates and assumptions, and that overlooked the impact of undetected cases outside of China (Grépin et al, 2021). Guidelines that recommended against the implementation of travel measures may have been made when considering travel measures in isolation, and might not be robust when considering the coordinated implementation of both travel measures and community non-pharmaceutical interventions as occurs for an elimination strategy (Grépin et al, 2023; Martignoni et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increased risk of COVID-19 case importation through international travel (5,6), many countries implemented border measures, including closing borders, screening programs, and post-arrival quarantine (7)(8)(9)(10). Border control measures were necessary to regulate the movement of individuals across international borders due to the need to contain the transmission of COVID-19, prevent the importation of new variants and conserve essential healthcare resources (11)(12)(13). Border closures and surveillance programs in response to a pandemic are complex (14,15) and their implementation and effectiveness are influenced by several factors (16,17).…”
Section: Introductionmentioning
confidence: 99%